Receptor-targeted, drug-loaded, functionalized graphene oxides for chemotherapy and photothermal therapy - Thapa RK (Dove Medical Press, 2016)
Raj Kumar Thapa,1 Ju Yeon Choi,1 Bijay Kumar Poudel,1 Han-Gon Choi,2 Chul Soon Yong,1 Jong Oh Kim1 1College of Pharmacy, Yeungnam University, Gyeongsan, Gyeongsanbuk-do, South Korea; 2College of Pharmacy, Hanyang University, Ansan, South Korea Abstract: Cancer is one of the leading causes of death worldwide. Although different chemotherapeutic agents have been developed to treat cancers, their use can be limited by low cellular uptake, drug resistance, and side effects. Hence, targeted drug delivery systems are continually being developed in order to improve the efficacy of chemotherapeutic agents. The main aim of this study was to prepare folic acid (FA)-conjugated polyvinyl pyrrolidone-functionalized graphene oxides (GO) (FA-GO) for targeted delivery of sorafenib (SF). GO were prepared using a modified Hummer’s method and subsequently altered to prepare FA-GO and SF-loaded FA-GO (FA-GO/SF). Characterization of GO derivatives was done using ultraviolet/visible spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, atomic force microscopy, zeta potential measurements, and determination of in vitro drug release. Hemolytic toxicity, in vitro cytotoxicity, cellular uptake, and apoptotic effects of FA-GO/SF were also investigated. The results revealed that GO was successfully synthesized and that further transformation to FA-GO improved the stability and SF drug-loading capacity. In addition, the enhanced SF release under acidic conditions suggested possible benefits for cancer treatment. Conjugation of FA within the FA-GO/SF delivery system enabled targeted delivery of SF to cancer cells expressing high levels of FA receptors, thus increasing the cellular uptake and apoptotic effects of SF. Furthermore, the photothermal effect achieved by exposure of GO to near-infrared irradiation enhanced the anticancer effects of FA-GO/SF. Taken together, FA-GO/SF is a potential carrier for targeted delivery of chemotherapeutic agents in cancer. Keywords: graphene oxide, folic acid, sorafenib, targeted drug delivery, near-infrared